Improving the wear resistance and chloride permeability of sulphoaluminate cement by spindle-like calcium carbonate modification. (August 2022) - Wang, Junfeng; Ma, Liangwei; Lu, Liulei; Fu, Qionglin; Li, Xiaoli; Zhang, Renshuang; Liu, Yawei
Abstract: The present work investigates two crucial parameters in durability of sulphoaluminate cement incorporating spindle-like calcium carbonate (SCC) powders. Hydration and microstructure are investigated by isothermal calorimeter, XRD, TG-DTA, SEM, and MIP. Results show that the wear resistance and anti-chloride permeability of mortars increase firstly and then decrease with SCC content increasing. These properties present a clear positive correlation with the compressive strength at corresponding age. Specifically, the optimum addition of 2% SCC by cement weight causes a great reduction in wearing loss and chloride diffusion coefficient by 21.47% and 25.93%, respectively. Moreover, the use of SCC powders accelerates the formation of hydration products, i.e. ettringite and gel. Furthermore, SCC filler significantly reduces more harmful pores but increases harmless pores, namely refining pore distribution. Further, similar to chopped microfibers, SCC may restrain the propagation of micro-cracks. As a consequence, these can be explained as key reasons for enhancing properties of SCC modified sulphoaluminate cement. Graphical Abstract: ga1